Identification of a Novel Hepacivirus in Southeast Asian Shrew (Crocidura fuliginosa) from Yunnan Province, China - Ling Guo; Bei Li; Peiyu Han; Na Dong; Yan Zhu; Fuli Li; Haorui Si; Zhengli Shi; Bo Wang; Xinglou Yang; Yunzhi Zhang (Pathogens, 2023)
The genus Hepacivirus contains single-stranded positive-sense RNA viruses belonging to the family Flaviviridae, which comprises 14 species. These 14 hepaciviruses have been found in different mammals, such as primates, dogs, bats, and rodents. To date, Hepacivirus has not been reported in the shrew genus of Crocidura. To study the prevalence and genetic evolution of Hepacivirus in small mammals in Yunnan Province, China, molecular detection of Hepacivirus in small mammals from Yunnan Province during 2016 and 2017 was performed using reverse-transcription polymerase chain reaction (RT-PCR). Our results showed that the overall infection rate of Hepacivirus in small mammals was 0.12% (2/1602), and the host animal was the Southeast Asian shrew (Crocidura fuliginosa) (12.5%, 2/16). Quantitative real-time PCR showed that Hepacivirus had the highest viral RNA copy number in the liver. Phylogenetic analysis revealed that the hepaciviruses obtained in this study does not belong to any designated species of hepaciviruses and forms an independent clade. To conclude, a novel hepacivirus was identified for the first time in C. fuliginosa specimens from Yunnan Province, China. This study expands the host range and viral diversity of hepaciviruses.